2006
DOI: 10.1590/s0074-02762006000500008
|View full text |Cite
|
Sign up to set email alerts
|

Use of an immunodominant p17 antigenic fraction of Neospora caninum in detection of antibody response in cattle

Abstract: A Neospora caninum 17 kDa protein fraction (p17) has been described as an immunodominant antigen (IDA) under reducing and non-reducing conditions. The aim of the present study was to investigate the diagnostic utility of p17 in cattle. In order to achieve this, p17 was purified by electroelution from whole N. caninum tachyzoite soluble extract and a p17-based Western blot

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The use of sNcAg as effective vaccine antigen is supported by several studies performed by our group and others (Alvarez Garcia et al, 2006;Baszler et al, 2000;Mansilla et al, 2012;Moore et al, 2011). Soluble antigens of N. caninum tachyzoites can activate CD4 + T-cells (Rocchi et al, 2011), which are thought to be important in protecting cattle against this parasite's infection (Rocchi et al, 2011;Staska et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The use of sNcAg as effective vaccine antigen is supported by several studies performed by our group and others (Alvarez Garcia et al, 2006;Baszler et al, 2000;Mansilla et al, 2012;Moore et al, 2011). Soluble antigens of N. caninum tachyzoites can activate CD4 + T-cells (Rocchi et al, 2011), which are thought to be important in protecting cattle against this parasite's infection (Rocchi et al, 2011;Staska et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…However, the use of live vaccines can have some disadvantages including reversion to high virulence creating sources of persistent infections, risk of transmission of prion diseases and high costs for industrial production. Although there was evidence of efficacy using a commercial vaccine based on a crude lysate of tachyzoites (Romero et al, 2004) a recent clinical trial concluded that vaccination after conception prevented 61% abortions in one of five herds and that vaccination may have increased the risk of early embryonic death (Weston et al, 2012), Fractions of N. caninum soluble native antigens (sNcAg) constitute a promising candidate antigen for vaccine development (Alvarez Garcia et al, 2006;Baszler et al, 2000;Mansilla et al, 2012;Moore et al, 2011;Otsuki et al, 2013), as it does not require inactivation treatments that could modify and ruin antigenic determinants. Proteins present in the soluble-fraction have been identified as stimulators of CD4 + -T cell responses (Rocchi et al, 2011;Tuo et al, 2005) and dendritic cell maturation, promoting the acquired immunity, which could not be achieved using inactivated parasites (Mansilla et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a continued effort to identify useful N. caninum antigens for the immunodiagnosis of neosporosis, we report here the molecular characterization of the 17-19 kDa antigenic protein fraction, p17, previously identified as the major IDA in onedimensional PAGE by sera from bovines naturally infected with Neospora (Alvarez- Garcia et al 2002;Alvarez-Garcia et al 2006). Further characterization of p17 was accomplished by 2 complementary approaches.…”
Section: Discussionmentioning
confidence: 99%
“…(Alvarez-Garcia et al 2002;Alvarez-Garcia et al 2006). Further characterization of p17 was accomplished by 2 complementary approaches.…”
mentioning
confidence: 99%